2016
DOI: 10.5153/sro.4109
|View full text |Cite
|
Sign up to set email alerts
|

‘I Can't Settle If It's Not Tidy; I Blame that on My Mum’: Exploring Women's Relational Household Work Narratives

Abstract: Household work literature has highlighted the importance of mothers to their daughters' accounts of their household work practice, arguing that women can both aim to emulate and avoid particular practices in their own household work. This paper further explores this topic, drawing on a small-scale qualitative study to explore the self-narratives that two generations of mothers construct around the theme of household work. It looks particularly at how accounts of household work practices are incorporated into b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Adulthood is associated with taking personal responsibility; ‘childish dependency on parental care is expected to give way at a certain age to independent adulthood' (Hockey and James : 167). Part of being a parent is acting to facilitate these values in their children (Kettle ). However, as Yvonne acknowledged her son questioned this later in life, and had to ‘come to terms' with the appearance of his teeth.…”
Section: Doing Family Differently Through Oral Health Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Adulthood is associated with taking personal responsibility; ‘childish dependency on parental care is expected to give way at a certain age to independent adulthood' (Hockey and James : 167). Part of being a parent is acting to facilitate these values in their children (Kettle ). However, as Yvonne acknowledged her son questioned this later in life, and had to ‘come to terms' with the appearance of his teeth.…”
Section: Doing Family Differently Through Oral Health Practicesmentioning
confidence: 99%
“…Building on this, we follow Smart who argues for a greater focus on thinking, feeling and imagining, the interior processes that are entwined with the practices that constitute family (and the non-familial relationships that are part of our personal lives). 1 Smart's 'connectedness thesis' (2007: 189) has been used to explore family experiences of living with life-threatening illness (Ellis 2013), narratives of household work practices (Kettle 2016) and family use of commercial ultrasound (Roberts et al 2017). These authors have shown how the concepts of memory, biography, embeddedness, relationism and the imaginary (Smart 2007) can be used to theorise how family is created through social action.…”
Section: Introductionmentioning
confidence: 99%
“…Natasha Mauthner and Andrea Doucet (1998) adapted and expanded on the VCR method, primarily for application in projects that included a sociological focus (Byrne et al, 2009;Kettle, 2016). Mauthner and Doucet's (1998) adaptation of the VCR method explored "individuals' narrative accounts in terms of their relationships to the people around them and their relationships to the broader, social, structural and cultural contexts within which they live" (p. 126).…”
Section: Data Analysis and Interpretation Methodsmentioning
confidence: 99%
“…While recommendations have been made to report the socioeconomic status of research participants (Brunton et al, 2011), socioeconomic class is a complex issue and there are difficulties in unambiguously assigning a class location to women on the basis of education and/or occupation over time (Kettle, 2016). While some studies have used income and education as an indicator for socioeconomic status (Toohill et al, 2018), other studies have used private health insurance coverage as a proxy measure for socioeconomic status (e.g., Yelland & Brown, 2014), or not assigned mothers to a socioeconomic class at all (e.g., Porter, 2008b).…”
Section: Nature Of Samplementioning
confidence: 99%
See 1 more Smart Citation